2014
DOI: 10.1038/modpathol.2013.185
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor signaling pathway is frequently altered in ampullary carcinoma at protein and genetic levels

Abstract: Our objective was to explore alteration of the epidermal growth factor receptor signaling pathway in ampullary carcinoma. Immunohistochemical studies were employed to evaluate expression of amphiregulin as well as expression and activation of epidermal growth factor receptor. A lab developed assay was used to identify mutations in the epidermal growth factor receptor pathway genes, including KRAS, BRAF, PIK3CA, PTEN and AKT1. Fifty two ampullary carcinomas were identified, including 25 intestinal-type and 24 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 56 publications
4
31
0
2
Order By: Relevance
“… 25 Moreover, several studies showed discrepant results regarding the prognostic role of KRAS mutation for RFS or OS. 13 , 14 , 26 30 In one of them, whereas KRAS mutation was not associated with prognosis, patients with specific KRAS G12D mutation had a shorter survival compared to KRAS non-G12D mutation patients and KRAS -wild type patients. 29 Furthermore, KRAS mutation appears as an early event in AA pathogenesis, as it has been reported present in 20% of adenomas and 80% of AA in a series of endoscopic papillectomy samples.…”
Section: Discussionmentioning
confidence: 98%
“… 25 Moreover, several studies showed discrepant results regarding the prognostic role of KRAS mutation for RFS or OS. 13 , 14 , 26 30 In one of them, whereas KRAS mutation was not associated with prognosis, patients with specific KRAS G12D mutation had a shorter survival compared to KRAS non-G12D mutation patients and KRAS -wild type patients. 29 Furthermore, KRAS mutation appears as an early event in AA pathogenesis, as it has been reported present in 20% of adenomas and 80% of AA in a series of endoscopic papillectomy samples.…”
Section: Discussionmentioning
confidence: 98%
“…The 24 pancreatobiliary subtype cancers had a 42% incidence of K-ras mutation ( Table 2). 48 Studies that analyzed both pancreatic and ampullary cancers for K-ras mutation reported that the overall incidence of K-ras mutation in their series was lower than that in reported in PCs. These lower figures were initially thought to reflect a lower incidence of K-ras mutation in PC, but the APGI genome study has confirmed the high incidence of K-ras mutation in PC.…”
Section: Genetic and Molecular Aberrations In Ampullary Cancer Subtypementioning
confidence: 90%
“…Unlike PC, ampullary cancers have a far lower incidence of K-ras mutation. The incidence of K-ras mutation in ampullary cancer was analyzed by Mikhitarian et al 48 Of 52 cancers, 25 were intestinal subtype with a 52% incidence of K-ras mutation. The 24 pancreatobiliary subtype cancers had a 42% incidence of K-ras mutation ( Table 2).…”
Section: Genetic and Molecular Aberrations In Ampullary Cancer Subtypementioning
confidence: 99%
“…Other EGFR active drugs have not led to a prolonged OS, when added to standard chemotherapy [ 7 ]. EGFR expression has also been shown to be more common in PB-type than in I-type ampullary adenocarcinoma [ 14 ] and overexpression has been associated with shorter OS in I-type but not in PB-type tumours [ 15 ].…”
Section: Introductionmentioning
confidence: 99%